Elements of crimes under international law / Gideon Boas, James L. Bischoff, Natalie L. Reid. - Boas, Gideon; Bischoff, James L. (Attorney-Adviser); Reid, Natalie L. (International criminal law practitioner library ;, 2008)
Volume II of the International Criminal Law Practitioner Library series focuses on the core categories of international crimes: crimes against humanity, genocide, and war crimes. The authors present a comprehensive and critical review of the law on the elements of these crimes and their underlying offences, and examine how they interact with the forms of responsibility discussed in Volume I. They also consider the effect of the focus in early ICTY and ICTR proceedings on relatively low-level accused for the development of legal definitions that are sometimes ill-suited for leadership cases, where the accused had little or no physical involvement in the crimes. The book's main focus is the jurisprudence of the ad hoc Tribunals, but the approaches of the ICC and the various hybrid tribunals are also given significant attention. The relevant jurisprudence up to 1 December 2007 has been surveyed, making this a highly useful and timely work.